2011
DOI: 10.1007/s12034-011-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of elastic modulus in a nickel alloy from ultrasonic measurements

Abstract: Elastic constants relate technological, structural and safety aspects to various materials phenomena and to their fundamental interatomic forces. Hence, they are of fundamental importance in almost all engineering applications. Thus its determination is of utmost importance. The aim of the present investigation is to study the behaviour of elastic constants and the variation on heat treatment in a nickel base super alloy Nimonic 263 by ultrasonic velocity measurements. From the present study it is evident that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…In this study the E r value of the as-cast and melt-spun samples was found to be 56.82 and 70.50 GPa, respectively. However, the highest E r value in the heat-treated melt-spun samples was found to be 97.28 GPa at 900 8C, which is close to that reported by Parveen et al [40] and Kumar et al [41].…”
Section: Phase Identification and Thermal Properties Of Ni-23al Alloyssupporting
confidence: 89%
“…In this study the E r value of the as-cast and melt-spun samples was found to be 56.82 and 70.50 GPa, respectively. However, the highest E r value in the heat-treated melt-spun samples was found to be 97.28 GPa at 900 8C, which is close to that reported by Parveen et al [40] and Kumar et al [41].…”
Section: Phase Identification and Thermal Properties Of Ni-23al Alloyssupporting
confidence: 89%
“…Longitudinal v L and transverse v T velocities of ultrasonic waves obtained and bulk volumetric mass density d were used to calculate the following quantities [70,29,71]:…”
Section: Resultsmentioning
confidence: 99%
“…For determining the elastic modulus, Eqs. have been used, where V t and V l are the velocities of the transverse and the longitudinal ultrasonic waves G=ρVt2B=ρ(V124/3Vt2)E=3ρVt2false(V124false/3Vnormalt2false)/false(V12Vnormalt2false)…”
Section: Resultsmentioning
confidence: 99%